Pemberdayaan Masyarakat Dalam Mengatasi Kemiskinan dan Kesenjangan Sosial Studi Kasus di Desa Malasin - Maifizar, Arfriani; Regi Yuliana Sukma (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2025)
In general, poverty is a very complex problem, because it is not only related to the problem of low fulfillment of daily living needs, low people's income but also helplessness from economic, social, cultural and political aspects. Various efforts have been made by the government, both the New Order regime government and the Reformation Era government, to tackle poverty, using various approaches, such as a top down approach and a bottom up approach, as well as formulating various program policies, both social assistance programs and empowerment-based programs. The empowerment program is carried out to fully involve the community, starting from identifying problems, formulating, planning to the implementation and evaluation stages of the program, which aims to improve community welfare